2013
DOI: 10.1002/adsc.201300233
|View full text |Cite
|
Sign up to set email alerts
|

Stereoretentive Copper(II)‐Catalyzed Ritter Reactions of Secondary Cycloalkanols

Abstract: A Ritter-like coupling reaction of cyclic alcohols and both aryl and alkyl nitriles to form amides catalyzed by copper (II) triflate is described. These reactions proceed in good yields under mild and often solvent-free conditions. With 2- and 3-substituted cycloalkanols, amide products are formed with near complete retention of configuration. This is likely due to fast nucleophilic capture of a non-planar carbocations (hyperconjomers) stabilized by ring hyperconjugation. A critical aspect of this novel cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The first is the possibility of deactivating the Lewis acid via the formation of an alkoxide. At the same time, as a by‐product of alkoxide formation, equimolar amounts of water are generated that can deactivate the Lewis acid by acting as a Lewis base . The second is that dehydration of the substrate can proceed, especially in highly concentrated solutions, to give ethers via a self‐coupling reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The first is the possibility of deactivating the Lewis acid via the formation of an alkoxide. At the same time, as a by‐product of alkoxide formation, equimolar amounts of water are generated that can deactivate the Lewis acid by acting as a Lewis base . The second is that dehydration of the substrate can proceed, especially in highly concentrated solutions, to give ethers via a self‐coupling reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In 2012, Y. Hanzawa et al 21 reported another Ritter reaction of alkenes with molecular iodine (I 2 , 20 mol%) as the catalyst. In their protocol, the reaction of chiral (+)-camphene with benzonitrile under solvent-free conditions in the presence of water (100 mol%) caused skeletal rearrangement of the camphene and amidation, resulting in racemic (AE)-N-isobornylbenzamide (19) in good yield (Scheme 15). Under the optimum conditions, the reaction of chiral (+)-camphene with several other aliphatic and aromatic nitriles can occur, producing the corresponding amide compounds in good yields.…”
Section: Ritter Reaction Of Alkenesmentioning
confidence: 99%
“…Many useful compounds have been synthesized through Ritter or Ritter-type reaction, including asymmetrical di-and tri-substituted ureas, 3-substituted-3amino-oxindoles, 4-acyl-aminotetrahydroindazoles, N-(4-iodo-1,3-diarylbutyl) acetamides, 4-amidopiperidine derivatives and aza-bicyclic alkaloids. [4][5][6][7][8]10,11,[13][14][15][16][17][19][20][21][22][23][24]27,[30][31][32][33][34][35][36] This review focuses on new ndings in Ritter or Ritter-type reaction in the last four years and provides a concise overview of recent progress in this area.…”
Section: Introductionmentioning
confidence: 99%
“…26 Unfortunately, CH 3 CN was used as the reaction solvent in this excellent work, resulting in only the corresponding acetamides; this drawback of the Ritter reaction is one of the most important issues to be addressed to improve both the diversity of the produced amides and the atom economy of the Ritter reaction, although some Ritter reactions using other nitriles have also been reported. 27,28 Surprisingly, the related Ritter reaction at the αposition of the carbonyl group has been unexplored. This may be due to: 1) although an umpolung at the αposition of the carbonyl group is a straightforward strategy to achieve this transformation, 29 it is challenging because the generated carbocation intermediate is highly unstable due to the destabilizing effect of…”
Section: Introductionmentioning
confidence: 99%